Combat aircraft since 1945 - Wilson, Stewart (Airlife Pub., 2000)
This comprehensive directory provides warbird fans with color photos, production data, service histories, countries of origin, and specifications for the majority of post-World War II fighters, bombers, and cargo carriers. With regard to major aircraft types, special focus is given to the different variants and the advantages of certain variant modifications. Paperback, 8-1/2 x 11, 154 pages, 200 color, b/w